2008
DOI: 10.4238/vol7-2gmr431
|View full text |Cite
|
Sign up to set email alerts
|

Unusual chromosome numbers in Paspalum L. (Poaceae: Paniceae) from Brazil

Abstract: ABSTRACT. Somatic chromosome numbers were determined for 20 new germplasm accessions of Paspalum, belonging to 17 species collected in Brazil. Chromosome number is reported for the first time for P. reduncum (2n = 18), P. cinerascens (2n = 20), P. cordatum (2n = 20), P. filgueirasii (2n = 24), P. ammodes (2n = 36), P. bicilium (2n = 40), P. heterotrichon (2n = 40), and P. burmanii (2n = 48). New cytotypes were confirmed for two germplasm accessions of P. carinatum (2n = 30) and P. trachycoleon (2n = 36), one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…ex Flüggé (Selva 1976;Reeder 1984). Recently, Peñaloza et al (2008), have reported chromosome numbers of five species with unexpected 2n = 18, 24, 36, and 48, which could be multiple to x = 6 or x = 9.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…ex Flüggé (Selva 1976;Reeder 1984). Recently, Peñaloza et al (2008), have reported chromosome numbers of five species with unexpected 2n = 18, 24, 36, and 48, which could be multiple to x = 6 or x = 9.…”
Section: Resultsmentioning
confidence: 98%
“…Chromosome numbers are known for nearly half the species (Honfi 2003). The basic chromosome number is generally x = 10, with a few exceptions (Honfi et al 1990;Quarin 1992;Norrmann et al 1994a;Pozzobon et al 2000;Peñaloza et al 2008). Polyploidy is a very common feature present in about 80% of the species, with levels varying from 3x to 16x and tetraploidy the most frequent condition.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…2D-E, 3D) suggest that P. minutispiculatum is morphologically closer to P. bicilium (Figs. 3C-right, E), according to the circumscription of the latter species as cited by Filgueiras (1991), Oliveira and Valls (2014), and supported by Peñaloza et al (2008), and not as a mere synonym of P. polyphyllum (Silva 2013). On the other hand, P. minutispiculatum differs from P. bicilium and P. polyphyllum by several characters (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Killeen (1990), Denham et al (2002), and Zuloaga and Morrone (2005) considered P. bicilium as conspecific with P. polyphyllum. Filgueiras (1991), Peñaloza et al (2008), Silva (2013), and Oliveira and Valls (2014) considered P. bicilium and P. polyphyllum independent species. Rua et al (2010) found evidence with molecular data that these species are distinct.…”
mentioning
confidence: 99%